2015
DOI: 10.1083/jcb.201311117
|View full text |Cite
|
Sign up to set email alerts
|

APPL endosomes are not obligatory endocytic intermediates but act as stable cargo-sorting compartments

Abstract: Endocytosis allows cargo to enter a series of specialized endosomal compartments, beginning with early endosomes harboring Rab5 and its effector EEA1. There are, however, additional structures labeled by the Rab5 effector APPL1 whose role in endocytic transport remains unclear. It has been proposed that APPL1 vesicles are transport intermediates that convert into EEA1 endosomes. Here, we tested this model by analyzing the ultrastructural morphology, kinetics of cargo transport, and stability of the APPL1 compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
126
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(145 citation statements)
references
References 67 publications
19
126
0
Order By: Relevance
“…S4C). In agreement with this interpretation, APPL1 has been recently described as an important factor for bidirectional sorting of endosomal cargo that is destined for plasma membrane delivery or for endocytic processing (Kalaidzidis et al, 2015). Finally, as a corollary to the study of APPL1 and PI3K signaling for LTP, we have found that inhibitors of the immediate downstream effectors of this pathway, PDK1 and Akt, do not affect synaptic potentiation.…”
Section: Discussionsupporting
confidence: 64%
“…S4C). In agreement with this interpretation, APPL1 has been recently described as an important factor for bidirectional sorting of endosomal cargo that is destined for plasma membrane delivery or for endocytic processing (Kalaidzidis et al, 2015). Finally, as a corollary to the study of APPL1 and PI3K signaling for LTP, we have found that inhibitors of the immediate downstream effectors of this pathway, PDK1 and Akt, do not affect synaptic potentiation.…”
Section: Discussionsupporting
confidence: 64%
“…These data point to a positive feedback loop resulting from the crosstalk between signaling and early endocytic trafficking and impinging on Dyn1 activity. APPL1, a Rab5 effector, labels a sub-population of Rab5-positive signaling and sorting endosomes that can be regulated by EGFR through Grb2 (Kalaidzidis et al, 2015; Martinu et al, 2002; Miaczynska et al, 2004; Schenck et al, 2008). Grb2 interacts with dynamin’s proline/arginine-rich domain (Solomaha et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Endosomal sorting could be more complex requiring several signaling molecules like phosphatidylinositol 3-kinase (36), receptor tyrosine kinase (37), and various effectors. Recent studies have shown that APPL1, a Rab5 effector, regulates the differential sorting of EGF and transferrin from endosomes (38). Moreover, cargo sorting might occur at the plasma membrane depending on the mode of entry as clathrin-coated vesicles are also differentially tethered to the two types of endosomes (39).…”
Section: Discussionmentioning
confidence: 99%